Korosi Alumunim dalam larutan asam sitrat - Andreas Yoppy Aprianto Prasetya; Isdiriayani Nurdin (Jurnal Teknik Kimia Indonesia, 2012)
The corrosion of Allumunium in citric acid sollutionCitric acid is a carboxylic acid that is widely used as an additive in the beverage industry. Aluminum cans are often used as a beverage packaging due to its lightweight, space efficient, and low production costs. Contact between citric acid and the aluminum cans may cause corrosion reactions that lead contamination of beverages by corrosion products. This study aims to test the aluminum resistance against citric acid at the concentration of 1, 2, and 4 %-wt, and temperature of 40 °C, 50 °C, and 60 °C. The specimen used is a 1 cm2 aluminum plate with a purity of 99.07%. The experiment consists of aluminum corrosion rate measurements using the Tafel method and aluminum corrosion mechanism prediction using cyclic-voltammetry method. The research results show that aluminum is corroded into Al3+ by citric acid solution in a one-stage reaction with activation energy of 65.01 kJ/mol. The corrosion products are not stable, it forms amorphous aluminum salts. The aluminum corrosion rate increases with rising citric acid concentration and temperature that can be classified in "negligible" to "medium" category.Keywords: aluminum, citric acid concentration, corrosion, temperature AbstrakAsam sitrat merupakan asam karboksilat yang banyak digunakan sebagai aditif pada industri minuman. Kaleng aluminium sering dipakai sebagai kemasan minuman karena sifatnya yang ringan, efisien ruang, dan biaya produksinya rendah.  Kontak asam sitrat dengan kemasan berupa kaleng aluminium dapat menyebabkan reaksi korosi yang berujung kontaminasi produk korosi terhadap minuman. Penelitian ini bertujuan untuk menguji ketahanan aluminium terhadap korosivitas asam sitrat pada konsentrasi 1, 2, dan 4 %-b, serta temperatur 40 °C, 50 °C, dan 60 °C. Logam yang digunakan merupakan pelat aluminium dengan kemurnian 99,07% dan luas permukaan 1 cm2. Penelitian mencakup pengukuran laju korosi aluminium dengan metoda Tafel dan prediksi mekanisme korosi aluminium dengan metoda voltametri siklik. Hasil penelitian yang dilakukan menunjukkan bahwa aluminium terkorosi dalam larutan asam sitrat menjadi Al3+ dengan satu tahap reaksi searah dan energi aktivasi sebesar 65,01 kJ/mol. Produknya bersifat tidak stabil, langsung membentuk garam aluminium amorf. Laju korosi aluminium meningkat seiring dengan meningkatnya konsentrasi asam sitrat dan temperatur, termasuk golongan korosi “dapat diabaikan” hingga “sedang”.Kata kunci: aluminium, konsentrasi asam sitrat, korosi, temperatur